2015
DOI: 10.1073/pnas.1506593112
|View full text |Cite
|
Sign up to set email alerts
|

Defining roles of PARKIN and ubiquitin phosphorylation by PINK1 in mitochondrial quality control using a ubiquitin replacement strategy

Abstract: The PTEN-induced putative kinase protein 1 (PINK1) and ubiquitin (UB) ligase PARKIN direct damaged mitochondria for mitophagy. PINK1 promotes PARKIN recruitment to the mitochondrial outer membrane (MOM) for ubiquitylation of MOM proteins with canonical and noncanonical UB chains. PINK1 phosphorylates both Ser65 (S65) in the UB-like domain of PARKIN and the conserved Ser in UB itself, but the temporal sequence and relative importance of these events during PARKIN activation and mitochondria quality control rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
301
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(322 citation statements)
references
References 26 publications
21
301
0
Order By: Relevance
“…Though pUb binding to parkin decreases the affinity of R0RBR for the Ubl domain, it is not sufficient to dislodge the Ubl domain in the crystal (Kumar et al , 2015, 2017). Rather, this step optimizes parkin for Ubl phosphorylation and E2~Ub engagement (Fig 6B; Kumar et al , 2015; Ordureau et al , 2015). It is well established that phosphorylation of the Ubl domain following pUb recruitment significantly increases its ubiquitination activity (Kondapalli et al , 2012; Shiba‐Fukushima et al , 2012; Kane et al , 2014; Kazlauskaite et al , 2014; Koyano et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Though pUb binding to parkin decreases the affinity of R0RBR for the Ubl domain, it is not sufficient to dislodge the Ubl domain in the crystal (Kumar et al , 2015, 2017). Rather, this step optimizes parkin for Ubl phosphorylation and E2~Ub engagement (Fig 6B; Kumar et al , 2015; Ordureau et al , 2015). It is well established that phosphorylation of the Ubl domain following pUb recruitment significantly increases its ubiquitination activity (Kondapalli et al , 2012; Shiba‐Fukushima et al , 2012; Kane et al , 2014; Kazlauskaite et al , 2014; Koyano et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…52 Thus, a combined action of phosphorylation and ubiquitination of inherent mitochondrial proteins such as Miro will have a direct impact on mitochondrial intracellular distribution. 53,54 We have recently demonstrated that VEEV capsid exists in an ubiquitinated state in U87MG cells. 8 It would be interesting to determine if capsid protein in mitochondria exists in an ubiquitinated state and if such an event is mediated by Parkin.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for a crucial role of K6-linked ubiquitin chains has been provided by a ubiquitin replacement strategy in U2OS cells, wherein all endogenous copies of ubiquitin were deleted and replaced by either exogenous wild-type or mutant ubiquitin. Using these cells, it has been demonstrated that mitophagy is significantly delayed in cells expressing K6R or K63R mutant ubiquitin (Ordureau et al, 2015a). The mitochondrion-localized DUB USP30 counteracts inappropriate ubiquitylation of healthy mitochondria (Bingol et al, 2014;Cunningham et al, 2015;Liang et al, 2015;Wang et al, 2015).…”
Section: K6 Linkages -Still Much To Learnmentioning
confidence: 99%